2022
DOI: 10.1186/s12951-022-01301-3
|View full text |Cite
|
Sign up to set email alerts
|

The sustained PGE2 release matrix improves neovascularization and skeletal muscle regeneration in a hindlimb ischemia model

Abstract: Background The promising therapeutic strategy for the treatment of peripheral artery disease (PAD) is to restore blood supply and promote regeneration of skeletal muscle regeneration. Increasing evidence revealed that prostaglandin E2 (PGE2), a lipid signaling molecule, has significant therapeutic potential for tissue repair and regeneration. Though PGE2 has been well reported in tissue regeneration, the application of PGE2 is hampered by its short half-life in vivo and the lack of a viable sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Several cell types can produce PGE2, such as fibroblasts and inflammatory cells, and the distinct secretion of PGE2 occurs during the immune response [ 54 , 55 ]. It has been reported that PGE2 may play proinflammatory and anti-inflammatory roles by binding to EP1-EP4 receptors [ 35 , 56 , 57 ]. Via PGE2 secretion, MSCs mediate the activation of macrophage (M2) polarization and inhibit the proliferation of activated T, NK and NKT cells [ 49 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cell types can produce PGE2, such as fibroblasts and inflammatory cells, and the distinct secretion of PGE2 occurs during the immune response [ 54 , 55 ]. It has been reported that PGE2 may play proinflammatory and anti-inflammatory roles by binding to EP1-EP4 receptors [ 35 , 56 , 57 ]. Via PGE2 secretion, MSCs mediate the activation of macrophage (M2) polarization and inhibit the proliferation of activated T, NK and NKT cells [ 49 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Via PGE2 secretion, MSCs mediate the activation of macrophage (M2) polarization and inhibit the proliferation of activated T, NK and NKT cells [ 49 , 58 ]. Recent work using the bioactive molecule PGE2 showed promise for angiogenesis functions and regenerative therapy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 200 μL of 1 mg/mL NO prodrug, MGP, was administered via tail vein injection every other day until the end of the experiment. To monitor angiogenesis in real time in vivo, C57BL/6 albino and outbred (Nu/Nu) background Vegfr2-luciferase transgenic mice (10 weeks of age, female) were used to establish an AKI model induced by I/R injury ( Zhang et al, 2023 ; Huang et al, 2022 ). The treatment of animals and the experimental procedures of the present study adhered to the Nankai University Animal Care and Use Committee Guidelines that conform to the Guidelines for Animal Care approved by the National Institutes of Health (NIH).…”
Section: Methodsmentioning
confidence: 99%
“…In Vegfr2‐Fluc‐KI mice, firefly luciferase (Fluc) was expressed under the promoter of vascular endothelial growth factor receptor 2 (Vegfr2) to report angiogenesis in vivo. [ 17 ] All the animal treatments and the experimental procedures of the present study were approved by the Animal Experiments Ethical Committee of Nankai University and were in accordance with the NIH Guide for the Care and Use of Laboratory Animals (approval no. 20 190 022).…”
Section: Methodsmentioning
confidence: 99%